The challenges of the transnational sub-state agenda. The production of new energies in the province of Jujuy (Argentina) (Revista LIDER, 2020)
This article proposes to study the transnational management of sub-state units on energy production. The case of analysis is the province of Jujuy (Argentina) in reference to the production of lithium carbonate and solar energy, between 2010 and 2017. The period under study begins with the first project of lithium carbonate production and it ends with the solar plant construction of Cauchari in 2017.The hypothesis of analysis indicates that sub-state units use transnationalmanagement as a strategy in order to pursue its development goals through energy projects with the State and other international actors.The objective is to describe Jujuy’s strategies, regarding the State and theinternational system, for the management of energy projects that enable local development.To this end, this article uses the theories of complex interdependence that support the existence of an international system composed of actors of different natures, and paradiplomacy studies to understand the international action of sub-state units and their link with local development.The methodology is qualitative, using interviews, analysis of bibliographic anddocumentary sources.